Continuity of Ice Sheet Mass Loss in Greenland and Antarctica From the GRACE and GRACE Follow‐On Missions. Issue 8 (21st April 2020) - Velicogna, Isabella; Mohajerani, Yara; A, Geruo; Landerer, Felix; Mouginot, Jeremie; Noel, Brice; Rignot, Eric; Sutterley, Tyler; van den Broeke, Michiel; van Wessem, Melchior; Wiese, David
Abstract: We examine data continuity between the Gravity Recovery and Climate Experiment (GRACE) and GRACE Follow‐On (FO) missions over Greenland and Antarctica using independent data from the mass budget method, which calculates the difference between ice sheet surface mass balance and ice discharge at the periphery. For both ice sheets, we find consistent GRACE/GRACE‐FO time series across the data gap, at the continental and regional scales, and the data gap is confidently filled with mass budget method data. In Greenland, the GRACE‐FO data reveal an exceptional summer loss of 600 Gt in 2019 following two cold summers. In Antarctica, ongoing high mass losses in the Amundsen Sea Embayment of West Antarctica, the Antarctic Peninsula, and Wilkes Land in East Antarctica cumulate to 2130, 560, and 370 Gt, respectively, since 2002. A cumulative mass gain of 980 Gt in Queen Maud Land since 2009, however, led to a pause in the acceleration in mass loss from Antarctica after 2016. Key Points: We demonstrate data continuity of the GRACE and GRACE‐FO missions over Greenland and Antarctica using independent data GRACE‐FO data capture a record‐high summer loss (600 Gt) in Greenland in 2019 Mass gain in Queen Maud Land mitigate high losses in the Amundsen Sea, Peninsula, and Wilkes Land to pause the acceleration in mass loss